Cellulose and protein nanofibrils: Singular biobased nanostructures for the design of sustainable advanced materials - Silva, Ana C. Q.; Silvestre, Armando J. D.; Vilela, Carla; Freire, Carmen S. R. (Frontiers in Bioengineering and Biotechnology, 2022)
Polysaccharides and proteins are extensively used for the design of advanced sustainable materials. Owing to the high aspect ratio and specific surface area, ease of modification, high mechanical strength and thermal stability, renewability, and biodegradability, biopolymeric nanofibrils are gaining growing popularity amongst the catalog of nanostructures exploited in a panoply of fields. These include the nanocomposites industry, paper and packaging, environmental remediation, electronics, energy, and biomedical applications. In this review, recent trends on the use of cellulose and protein nanofibrils as versatile substrates for the design of high-performance nanomaterials are appraised. A concise description of the preparation methodologies and characteristics of cellulosic nanofibrils, namely nanofibrillated cellulose (NFC), bacterial nanocellulose (BNC), and protein nanofibrils is presented. Furthermore, the use of these nanofibrils in the production of sustainable materials, such as membranes, films, and patches, amongst others, as well as their major domains of application, are briefly described, with focus on the works carried out at the BioPol4Fun Research Group (Innovation in BioPolymer based Functional Materials and Bioactive Compounds) from the Portuguese associate laboratory CICECO – Aveiro Institute of Materials (University of Aveiro). The potential for partnership between both types of nanofibrils in advanced material development is also reviewed. Finally, the critical challenges and opportunities for these biobased nanostructures for the development of functional materials are overviewed.